Toward a Greener Building Envelope: Analyzing Sustainable Cladding Materials through BIM for Energy Efficiency - Balo, Figen; Sagbansua, Lutfu; Boydak, Hazal (Bilingual Publishing Group, 2024)
The proper building materials used in the building envelope provide better thermal and energy efficiency of the building by allowing for better thermal regulation between the inside and exterior. The scope of this research involves the optimization of the building envelope’s features to enhance the thermal ambiance and lower the energy requirements of residential structures in a specific environment. Critical design choices include the facade cladding system and building insulation materials. In order to select the most effective facade cladding system among widely used materials in the Black Sea climate conditions, this study attempts to develop sustainable design options by building information modeling of a sample site security cabin modeled with the BIM-based Autodesk Revit software, followed by a building energy model. Finally, building energy simulation was carried out with Green Building Studio, which can be integrated with the Autodesk Revit program. The heating, cooling, and total energy consumption of the sample site security cabin project were determined by the analysis. Seventy-two alternative designs resulting from eight different coating materials, three commercial insulation materials, and three different structural materials were evaluated. In terms of energy efficiency, EPS and siding were obtained as the most effective insulation materials and coating materials for Trabzon province. This way, it has been aimed to provide the designers with the information through the sample project for the buildings to be designed in the determined climatic conditions. © 2024 by the author(s).
Keywords: Building Envelope; Building Information Modeling; Cladding Materials; Energy Efficiency; Insulation Materials